2018
DOI: 10.1186/s40410-018-0084-6
|View full text |Cite
|
Sign up to set email alerts
|

Land-allocation and clan-formation in modern residential developments in Oman

Abstract: Affordable housing with fair and transparent land-allocation measures is a challenge for many countries. The Sultanate of Oman solves this issue by means of land-allocation lotteries in which male and female citizens can participate in order to win a parcel of a new housing area. Besides supporting those in financial need the lottery aims to mix the separate tribes of Oman and thus contribute to the nation building of a modern society. In an earlier work, we showed that there must be severe doubts about the ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Despite the dominant mono-functional character of the new residential neighborhoods in Muscat, the areas where we carried out the surveys (delimited by a 400 m radius around the mosque) concentrated a small cluster of commerce and services. Previous research [74] revealed that walking to prayers is the most common active mobility activity performed by residents of Muscat. Additionally, it is prescribed by law to allocate a small number of shops and services such as a tailor, grocery, coffee shop, and so forth to cover the daily needs of residents and to help to sustain the mosque economically.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the dominant mono-functional character of the new residential neighborhoods in Muscat, the areas where we carried out the surveys (delimited by a 400 m radius around the mosque) concentrated a small cluster of commerce and services. Previous research [74] revealed that walking to prayers is the most common active mobility activity performed by residents of Muscat. Additionally, it is prescribed by law to allocate a small number of shops and services such as a tailor, grocery, coffee shop, and so forth to cover the daily needs of residents and to help to sustain the mosque economically.…”
Section: Discussionmentioning
confidence: 99%
“…Royal Decree 81/84-the Government Land Entitlement System effective since 1984 stated that all Omani male citizens could apply for and receive free 600 sqm housing plots at the age of 23. The plots were randomly allocated, which demographically intertwined neighborhoods of Muscat (Heim et al 2018). These plots were also regulated by building laws that mainly allowed for single-family detached houses known as Villas.…”
Section: Muscat An Expanding Metropolismentioning
confidence: 99%
“…After the founding of the People's Republic of China, the clan system disintegrated, and the changes in prosperous clans resulted in groundbreaking transformations in the spatial patterns of villages [22]. Courtyard houses are the direct venue for clan activities, and as the most common rural spatial system component closest to people's daily lives, the distribution of the courtyard house is a mapping of the aggregation and differentiation of blood ties [23], with the distribution of social relations such as kinship ties being transformed into a visible space in the rural layout through the distribution of the courtyard house structures. Since ancient times, Henan has existed in the hinterland of the Central Plains and is one of the birthplaces of Chinese civilization, with a long history and cultural heritage and strong clan characteristics that shape the spatial layout of traditional villages in a manner that is compatible with the north and south.…”
Section: Introductionmentioning
confidence: 99%